Three-dimensional assessment of restored smiling mobility after reanimation of unilateral facial palsy by triple innervation technique. Issue 4 (April 2020) - Gibelli, D.; Tarabbia, F.; Restelli, S.; Allevi, F.; Dolci, C.; Dell'Aversana Orabona, G.; Cappella, A.; Codari, M.; Sforza, C.; Biglioli, F.
Abstract: The aim of this study was to assess surgically restored facial mobility using an optical 3D instrument. Eleven patients (age range 42–76 years) with unilateral facial palsy, treated by triple innervation procedure (masseteric and partial hypoglossal reinnervation, plus double cross-face facial grafting), performed five facial animations: rest position, smiling by contracting the healthy side, clenching the teeth, and pushing the tongue against the lower incisors and Mona Lisa smiling. These were recorded by stereophotogrammetry. Sixty healthy subjects were also recorded. The 3D reconstruction of each facial expression was registered onto the rest position scan, and the root mean square (RMS) point-to-point distance between the two 3D surfaces was calculated automatically for the facial thirds. RMS values on the rehabilitated hemiface were 74.8% (upper third), 46.6% (middle third), and 54.1% (lower third) of those recorded in healthy subjects. RMS values were higher in the middle and lower thirds than in the upper third, and during smile provided by masseteric stimulus ( P < 0.05). The rehabilitated hemiface differed more from healthy subject values than the healthy hemiface did ( P < 0.05). On average, patients were more asymmetric than healthy subjects ( P = 0.004). The proposed method is non-invasive and non-contact, and it can quantify localized facial movements after surgical procedures.